2020
DOI: 10.1177/1477760620953437
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silicon dioxide addition and processing methods on structure, thermal stability and flame retardancy of EVA/NR blend nanocomposite foams

Abstract: Rubber nanocomposite foams based on 60/40 ethylene vinyl acetate (EVA)/natural rubber (NR) were melt-mixed with flame retardant silicon dioxide (SiO2) (20 parts per hundred rubber, phr), and foamed by compression molding process. In this study, the effect of mixing phenomena of SiO2 through two different compounding techniques such as direct mixing (DM) and phase selective mixing (PSM) methods on structure, thermal stability, combustility and flame retardancy of EVA/NR blend nanocomposite foams were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…As given in Table 3, there was an increase in the LOI values of EVANRSiO 2 foams with increasing SiO 2 loading, indicating that the flame retardancy of foamed materials were improved. According to previous work, 19 it was proved that the addition of SiO 2 filler (20 phr) in the EVA/NR blend nanocomposite foams could improve the thermal resistance by creating an insulating silicon dioxide-containing char layer on their burning surfaces. When the SiO 2 loading was increased, the silicon dioxide-based char layer with higher thermal resistance was obtained.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…As given in Table 3, there was an increase in the LOI values of EVANRSiO 2 foams with increasing SiO 2 loading, indicating that the flame retardancy of foamed materials were improved. According to previous work, 19 it was proved that the addition of SiO 2 filler (20 phr) in the EVA/NR blend nanocomposite foams could improve the thermal resistance by creating an insulating silicon dioxide-containing char layer on their burning surfaces. When the SiO 2 loading was increased, the silicon dioxide-based char layer with higher thermal resistance was obtained.…”
Section: Resultsmentioning
confidence: 97%
“…The average domain size of the NR in the EVANRSiO 2 -0 was about 2.58 ± 1.16 µm, while the average size of the NR domain in the EVANRSiO 2 -20 and EVANRSiO 2 -40 was around 2.27 ± 0.86 and 1.29 ± 0.24 µm, respectively. Based on the sequence of filler addition (Figure 1) and the TEM images (Figure 2), it is suggested that a number of flame retardant SiO 2 transferred from the EVA toward the NR preferred phase due to its low affinity, 19 and some SiO 2 fillers were absorbed at the EVA/NR interfaces of EVANRSiO 2 -20 and EVANRSiO 2 -40 as indicated by arrows. In an immiscible polymer blend, the solid fillers confined at the interface of two polymers act as physical barrier to prevent the coalescence of the minor phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silicone-containing flame retardants form an amorphous silicon protective layer on the surface of the material after burning to isolate the transfer of air and oxygen. Amorphous silica dioxide (SiO 2 ), due to its high heat resistance, inert and non-toxic properties, is considered as a potential and safe flame retardant [21]. The combination of silicon with other flame retardants will play a synergistic flame-retardant effect.…”
Section: Introductionmentioning
confidence: 99%